Eye health indicators for universal health coverage: results of a global expert prioritisation process. Issue 7 (12th March 2021) - McCormick, Ian; Mactaggart, Islay; Resnikoff, Serge; Muirhead, Debbie; Murthy, GV; Silva, Juan Carlos; Bastawrous, Andrew; Stern, Jude; Blanchet, Karl; Wang, Ningli; Yusufu, Mayinuer; Cooper, Andrew; et al.
Abstract : Introduction: In its recent World Report on Vision, the WHO called for an updated approach to monitor eye health as part of universal health coverage (UHC). This project sought to develop a consensus among eye health experts from all world regions to produce a menu of indicators for countries to monitor eye health within UHC. Methods: We reviewed the literature to create a long-list of indicators aligned to the conceptual framework for monitoring outlined in WHO's World Report on Vision . We recruited a panel of 72 global eye health experts (40% women) to participate in a two-round, online prioritisation exercise. Two-hundred indicators were presented in Round 1 and participants prioritised each on a 4-point Likert scale. The highest-ranked 95 were presented in Round 2 and were (1) scored against four criteria (feasible, actionable, reliable and internationally comparable) and (2) ranked according to their suitability as a 'core' indicator for collection by all countries. The top 30 indicators ranked by these two parameters were then used as the basis for the steering group to develop a final menu. Results: The menu consists of 22 indicators, including 7 core indicators, that represent important concepts in eye health for 2020 and beyond, and are considered feasible, actionable, reliable and internationally comparable. Conclusion: We believe this list can inform the development of new national eye health monitoring frameworks, monitor progress on key challenges to eye health and be considered in broader UHC monitoring indices at national and international levels.